Factors influencing Indigenous engagement in tourism development: an international perspective - Fletcher, C.; Pforr, Christof; Brueckner, M. (Routledge, 2016)
Indigenous tourism products, attractions and activities can offer a point of difference for tourism destinations, and consequently the role of, and opportunities for, Indigenous people in providing these tourism experiences have been recognised increasingly by government and industry alike. This paper reviews and discusses the factors influencing successful Indigenous tourism development and provides a global comparison of best practice to inform future decision-making processes in achieving sustainable Indigenous tourism development. Data was derived from interviews with key government and non-government organisations, and Indigenous tourism organisations and operators were analysed as a means of critically engaging with the sustainability problematic of Indigenous tourism development. Furthermore, a comprehensive analysis of international case studies focusing on Indigenous accommodation provision was carried out to complement the research, as were observations during site visits. By offering a framework for the Indigenous tourism development process, we contribute in a positive and flexible way to the complex, and evolving, discourse on Indigenous tourism practice. It is argued that the effectiveness of governance structures and the level of involvement of Indigenous stakeholders as well as the selection of legislative and policy instruments are key to ensuring a more sustainable approach to Indigenous tourism development.